2021
DOI: 10.1002/elps.202100049
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparations of polyhalogenated 4,4’‐bipyridines on polysaccharide‐based chiral stationary phases and molecular dynamics simulations of selector–selectand interactions

Abstract: 2’‐(4‐Pyridyl)‐ and 2’‐(4‐hydroxyphenyl)‐TCIBPs (TCIBP = 3,3’,5,5’‐tetrachloro‐2‐iodo‐4,4’‐bipyridyl) are chiral compounds that showed interesting inhibition activity against transthyretin fibrillation in vitro. We became interested in their enantioseparation since we noticed that the M‐stereoisomer is more effective than the P‐enantiomer. Based thereon, we recently reported the enantioseparation of 2’‐substituted TCIBP derivatives with amylose‐based chiral columns. Following this study, herein we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…With the aim to explore the binding mechanism of ( R )‐ 7 at the molecular level, 48,52–55 a MD simulation was performed by using the ( R )‐ 7 as selectand, an ADMPC nonamer as selector, and MeOH as a virtual solvent (Figure 5). The modeling of the experimental binding confirmed that the ( R )‐enantiomer of compound 7 penetrates deeply in the groove of the selector (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…With the aim to explore the binding mechanism of ( R )‐ 7 at the molecular level, 48,52–55 a MD simulation was performed by using the ( R )‐ 7 as selectand, an ADMPC nonamer as selector, and MeOH as a virtual solvent (Figure 5). The modeling of the experimental binding confirmed that the ( R )‐enantiomer of compound 7 penetrates deeply in the groove of the selector (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies integrating experimental analysis, V analysis, and MD simulations demonstrated that XB as a selector−selectand intermolecular interaction is less effective in the presence of strong HBs or π−π interactions within amylose-based selectors, 1397 whereas it has shown effective tuning ability on cellulose-based selectors, even in the presence of HB interactions contributing to enantiodiscrimination. 1398 The importance of introducing solvent parametrization correctly, and of using oligomers of adequate length to model polysaccharide-derivatives, had been already stressed in some earlier studies on enantioselection modelling performed by Grinberg and co-authors. 664 Two factors, more than others, make modelling polysaccharide-based selectors challenging: (a) the intrinsic structural complexity of these selectors and (b) the dependence of their recognition ability by their supramolecular high-order structure.…”
Section: Computation-based Modelling Of Enantioseparation Processes A...mentioning
confidence: 99%
“…Given the importance of MP composition on chiral recognition, the effect of solvent should be considered in the modelling of enantioselection. In this regards, MD simulations involving polysaccharide oligomers as models have been recently performed either explicitly 660,1190,1398,1404,1405 or implicitly. 1387,1406 Molecular docking studies were also performed to model the enantioseparation of chiral analytes with polysaccharide carbamate derivatives as selectors.…”
Section: Computation-based Modelling Of Enantioseparation Processes A...mentioning
confidence: 99%
“…Later, studies integrating experimental analysis and computational techniques, such as V analysis and MD simulations, demonstrated that XB, as a selector–selectand intermolecular interaction, is less effective in the presence of strong HBs or π–π interactions in the enantioseparation of 4,4′-bipyridine derivatives with amylose-based selectors, whereas it has shown effective tuning ability with cellulose-based selectors, even in the presence of HBs contributing to enantiodifferentiation [ 65 ].…”
Section: Enantioseparationmentioning
confidence: 99%